Analisis Penggunaan Modul Ajar Digital IPAS pada Materi Letak Kabupaten dan Provinsi di Kelas III Sekolah Dasar - Sari, Indah; Sukma, Elfia; Kharisma, Inggria (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyze the use of digital teaching modules, students’ perceptions, teachers’ readiness, as well as the availability of facilities and infrastructure in science and social studies (IPAS) learning at elementary schools. The research employs a qualitative approach with a descriptive-analytical design. The study was conducted through fieldwork at UPT SDN 04 Jaho, UPTD SDN 05 Sarilamak, and UPT SDN 16 Pulau Karam.The research subjects consisted of teachers from the three schools and 20 third-grade students of UPTD SDN 05 Sarilamak. Data were collected through observation, interviews, and questionnaires, and then analyzed using data reduction, data presentation, and conclusion drawing techniques. The results indicate that digital teaching modules are aligned with the curriculum and are able to present abstract material more concretely through visual media. Students’ perceptions of digital-based learning are generally positive, as reflected in increased interest, motivation, and engagement in learning. The use of digital media also encourages student independence. However, teachers’ readiness remains limited due to a lack of training and varying levels of digital competence. The availability of facilities and infrastructure is also inadequate, such as limited devices and internet access. Efforts that can be made include continuous training, provision of facilities, and the development of flexible offline-based modules.